Hubungan Penggunaan Gadget Dengan Perkembangan Anak Prasekolah Usia 5-6 Tahun Di TK Dharma Wanita I Tempurejo - Aprianingrum, Aulia Istihana; Kiswati, Kiswati; Umami, Riza (Malang Journal of Midwifery (MAJORY), 2023)
Preschool children have a very fast growth and development phase. One of the factors that influences children's development is playing with gadgets. In modern times like today, playing with gadgets has become routine. The 2020 Indonesian Internet Service Providers Association survey showed that 73.7% of smartphone users in Indonesia were preschool children. Based on the results of a preliminary study of 5 mothers who have preschool children, it was found that the children used gadgets for >1 hour every day and were already clever at operating gadgets. The purpose of this study was to determine the relationship between the use of gadgets and the development of preschool children aged 5-6 years. The research design used is correlation with a cross-sectional approach. Respondents were 33 children aged 5-6 years at Dharma Wanita I Tempurejo Kindergarten using purposive sampling technique. Data analysis used the Spearman rank test. The results of the research show that the majority of gadget use is in the moderate category (>40-60 minutes/day) as much as 39.4%, most of the development of preschool children aged 5-6 years is in the normal category as much as 81.8%, and the results of the p-value analysis value= 0.001<0.05 which means there is a relationship between gadget use and the development of preschool children aged 5-6 years with a correlation coefficient value of -0.568 indicating there is a negative relationship which means that the higher the intensity of gadget use, the development of preschool children will decrease. The use of gadgets in preschool children does not always have a bad impact. Parents need to accompany children in playing with gadgets. Parents must set time limits and choose applications to provide stimulation to children that is appropriate for their age.